PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH, TEKNOLOGI INFORMASI DAN SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN MOJOKERTO - PUTRA RIZKI, DIYAN (Jurnal Akuntansi AKUNESA, 2016)
ABSTRACT The aim of this research is to know the government internal control system, information technology usage, and effect of human resource capacity towards the quality of financial statement of Mojokerto. This research use quantitative approach using primary data obtained from spreading quenstionnaires. Sample selected is 123 employees who work as head officer and staff of accounting / financial administration sub section in 41 SKPD of Mojokerto. The research uses multiple linier regression analysis on SPSS 21. The result shows that government internal control system, informasion tecnology usage, and human resource capacity affect positively towards the quality of finanncial statement of Mojokerto Key Word: capacity, government, quality.